Berinteraksi dengan Hadis Dha’if dalam Kehidupan Sehari-Hari - Permana, Dede (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2020)
Muslims need to implement procedures based on principles of the Qur'an and Hadith to do worship and mu’amalah everyday,. The Qur'an as the word of God generally tells an outline (‘ām) in guiding humans to do their daily activities ideally, then explained in more detail (khāsh) about the technicalities of the application of these practices in various noble hadiths. Hadith covers what the Prophet Muhammad SAW do, say, agree, and what has become of the nature of the Prophet. This indicates that the Hadith is a complete package of life guidelines that we can follow. The Hadith certainly has an important role in applying the commands mentioned in the Qur'an, but it should be noted that some of the Hadith are acceptable such as the authentic hadith and hasan, and some need further review of the condition of the hadith such as the dla'if , and there are also false traditions (maudlū ') which we clearly reject because they are fabricated cases. Dla'if different from maudlū ', both in the status of the hadith and in practice. In the discussion this time we will review more deeply about the dla'if hadith and the limits of its practice. This discussion uses the literature study method with a descriptive qualitative approach, so that various discussions relating to the theme are collected and processed more proportionally to produce conclusions that answer the existing problems. This paper will answer the question, what is the urgency of embedding 'dha'if' for a hadith?